Arab-Iranian rivalry in the Persian Gulf - Sharifi-Yazdi, Farzad Cyrus. (London)
xi, [1], [2] sayfa harita, 402 sayfa
Keywords: “Iranian ambitions in the Persian Gulf and rivalries with Arab neighbours are subject to intense - and heated - speculation, controversy and debate. Here, Farzad Sharifi Yazdi scrutinises the rival Arab-Iranian claims to Bahrain, the Shatt al-Arab waterway, and the Abu Musa and Tunbs islands in the years after World War II and before the Iranian revolution. Through investigation of previously unexamined primary materials and interviews with leading players, this book sheds new light on the evolution and dynamics of hegemonic and nationalistic Arab-Iranian rivalries and how these rivalries began to find symbolic expression through territorial disputes. Sharifi illustrates that these ongoing disputes - and the deep-seated tensions still prevalent in Arab-Iranian relations - are largely rooted in how they were constructed in the post-World War II period, making this book vital reading for researchers of the politics, history, international relations and diplomacy of the Middle East“ --Yayıncıç